Supporting without barriers – from social activity to professional activation of people with disabilities - Parus-Jankowska, Magdalena (Niepełnosprawność i praca: Wymiary, konteksty, perspektywy, 2024)
People with disabilities still belong to the group of people at risk of exclusion due to difficult access to employment. Any form of support and activation of people with disabilities is desirable, especially when it can help them find their way in the labor market. In recent years, many initiatives have been created, such as disabled fans’ clubs and similar organizations bringing together people with disabilities interested in sports, whose goals go far beyond pure sports entertainment. They have become a place enabling social integration and the development of social competences and giving people with disabilities the opportunity to acquire various skills useful for becoming independent and taking full advantage of social life, as well as increasing their chances on the labor market. Finding oneself in a community of fans can build a sense of belonging and strengthen the support network, which contributes to an increase in the number of social contacts and the formation of weak ties, which may contribute to increasing the chances of taking up professional activity among people with disabilities.